Does schooling foster environmental values and action? A cross-national study of priorities and behaviors. (May 2018) - Post, David; Meng, Yi
Abstract: Steering the course of climate change will require coordination and collective action between nations, which are directed not only by the interests of their political leaders and elites but also the values of citizens. Previous studies have investigated macro-level factors that help explain international differences in general environmental concern. The present article draws on the sixth wave of the World Values Survey, which offers researchers an even starker outcome measure than general concern: whether or not environmental protection should be prioritized over economic growth. Here we report on WVS data from 50 countries to show the individual-level and national-level factors associated with respondents' prioritizations of the environment.